17β-estradiol residue determined in minced meat and it’s Carcinogencity in mice - Yaseen, Nahi Y. (Iraqi Journal of Cancer and Medical Genetics, 2013)
The main objective of this research to study carcinogenic effects of 17β-estradiol in mice by studying on haematological parameters (Hb, PCV, RBC, WBC and DWBC), mitotic index and histopathological changes of ovary, uterus and mammary gland. The following results which obtained from the current research: The effects of 17β-estradiol for six months on blood picture had no-significant differences on the blood haemoglobin (Hb) (11.55 and 11.69 gm/dl), total number of red blood cells (RBC) counts in the peripheral blood. RBC counts were 7.48 and 6.98 × 106/mm3 for the two groups respectively. Basophiles percent (3.40 and 3.54%) also (8.68 and 8.09%) for Monocytes percent for the two experimental groups respectively. Significant decrease (P˂0.05) in PCV% were noticed between the control and treated group (37.40and 31.28 %) respectively, and Lymphocyte percent (49.00 and 46.03%). Also significant increases (P˂0.05) were observed in the WBC count between the control and the second group (7.05 and 9.43 109/l), and the Neutrophil percent (35.52 and 37.35%) respectively, also significant increases (P˂0.05) in the Eosinophil percent (3.40 and 4.99 %) respectively. The results of carcinogenic effects on cytogenic study showed a significant increase (P˂ 0.05) in mitotic index for mice treated with17β-estradiol in comparison to control group. While the histopathological changes, in ovary: In mice treated with 17β-estradiol revealed immature development of follicles that primordail and primary follicles can be detect while secondary follicle was noted without ova and no griffin follicle can be seen. The histopathological study of uterus: In mice treated with 17β-estradiol showed dilatation of endometrial glands with hyperplasia of epithelial cells lining uterus and there is compact hypercellular stroma. While the histopathological changes, in mammary gland: The mammary gland of treated mice with 17-β estradiol showed pleomorphic hyperchromatic malignant cells in addition somewhere arranged as glandular structure, but the gross appearance of mammary gland adenocarinoma gives enlargement with irregular shape.